Estudo de métodos não convencionais visando o controle do ácaro Oligonychus ilicis (McGregor, 1917) (Acari: Tetranychidae) em cafeeiro (Coffea arabica L.) - Toledo, Melissa Alves de (2015)
The coffee red spider mite, Oligonychus ilicis (McGregor, 1917) (Acari: Tetranychidae) can cause a significant reduction in the photosynthesis potential and the growth of new plants. The most widely used method to control this mite is usually chemical, so it’s necessary the study of less toxic alternatives. Noteworthy the study of predatory mites for the biological control and induced plant resistance by silicon applications. Therefore the aim of this study were to evaluate the predation potential of E. alatus as a biological control agent of O. ilicis, the influence of the byproducts (webs, faeces and exuviae of O. ilicis) in the location of O. ilicis by E. alatus and the interference of silicon in the infestation of O. ilicis in coffee plants. For the predation potential bioassay each stage of E. alatus (larva, nymph, adult male and female) were tested with each stage of O. ilicis development (egg, larva, nymph and adult), with ten repetitions. The functional and numerical responses of E. alatus were evaluated on coffee leaves arenas and offered 1 to 125 immature stages of O. ilicis per arena. The number of preys killed and the number of eggs laid by predator were evaluated. The foraging bioassay was performed in an olfactometer Y-tube. Studies of plant resistance were conducted in a greenhouse, and applied potassium silicate at doses of 0, 2, 4, 6, 8 and 10 mL/ha. The number eggs, larvae plus nymphs and adults alive were evaluated under stereoscopic microscope. Larvae and nymphs of O. ilicis were the most efficient in predation of all stages of the mite predator. Regression analysis suggests a functional response type II. Leaves with mites and mites more byproducts were able to emit volatile chemicals attractive to the predator. But leaves with byproducts were not attractive to the predatory mite. The applications of potassium silicate, silicon source, showed a positive effect in controlling O. ilicis in coffee plants, even being a dicot.